(untitled) (The Agriculturists, 2013)
An investigation was carried out to evaluate the insecticidal activity of Allium sativum, Zingiber officinale and Nigella sativa extracts against the larvae of T. granarium under laboratory conditions in the University of Agriculture, Faisalabad, Pakistan during 2009-10. The highest concentration of (6 %) Z. officinale was found to be comparatively more toxic (16.70 %) than those of A. sativum (10.45 %) and N. sativa (5.49 %) at 96 hours exposure. Regarding latent effect of the test plant materials, Z. officinale gave significantly higher reduction (54.15 %) in F1 progeny than N. sativa (41.97 %) and A. sativum (32.19 %). The study reveals that Z. officinale had a strong latent effect against the larvae of the test pest. Further investigations on the efficacy of longer exposure in combination with higher concentrations of these extracts can be helpful to reduce the wheat store-insect damage. DOI: http://dx.doi.org/10.3329/agric.v11i1.15250 The Agriculturists 2013; 11(1) 103-111